2022
DOI: 10.4274/jcrpe.galenos.2022.2022-12-4
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Newly Diagnosed Type 1 Diabetes Mellitus in Children and Adolescents in Henan Province of China from 2017 to 2020: A Retrospective Multicenter Study Based on Hospitalization Data

Abstract: Objective: The incidence of type 1 diabetes mellitus (T1DM) is rapidly increasing worldwide. However, the incidence in Henan Province of China has been unknown for more than two decades. This study aimed to estimate the incidence of T1DM in the 0.5-14.9 years age group in Henan Province of China from 2017 to 2020. Methods: A retrospective analysis of hospital registration data from 18 cities in Henan Province, China, identified 1726 patients (843 males, 883 females) bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Nishioka and colleagues reported that in Japan, the incidence of T1DM in patients aged 0–19 for men was 3.94/100,000 person-years, while that for women was 5.22/100,000 person-years [ 36 ]. A study from China’s Henan province showed that the female-to-male incidence rate ratio was 1.32 (95% CI 1.20, 1.45) in the 0–14 years age group [ 37 ]. In this study, the male-to-female ratio of the incidence of T1DM was 1:1.31, which was consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Nishioka and colleagues reported that in Japan, the incidence of T1DM in patients aged 0–19 for men was 3.94/100,000 person-years, while that for women was 5.22/100,000 person-years [ 36 ]. A study from China’s Henan province showed that the female-to-male incidence rate ratio was 1.32 (95% CI 1.20, 1.45) in the 0–14 years age group [ 37 ]. In this study, the male-to-female ratio of the incidence of T1DM was 1:1.31, which was consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%